Comparative analysis of the effects of business of public enterprises in Serbia - Jovović Marina; Prlinčević Gordana; Mušikić Slađana (Trendovi u Poslovanju)
Since the beginning of the transition, Serbia has been trying to include the public sector in that process. Although efforts have been made to restructure public companies, the situation is still unsatisfactory and this sector has remained mostly untransformed and ineffective. The public sector has a high share in the formation of the country's gross social product, has large assets and employs one third of the total number of employees. Although state-owned enterprises have huge assets and have a monopoly position on the market, they generally operate at a loss. Realized losses indicate that the very large resources of the country are poorly managed. Due to the vital importance of state enterprises for the economic development of the country, it is necessary to implement structural reforms and make these enterprises become generators of development.